Kultur Nongkrong Warkop Analisis Dinamika Sosial dan Perilaku Konsumtif Generasi Muda Pendekatan Konseling Islam - Muslima (Jurnal Pengembangan Profesi Guru dan Dosen, 2025)
The coffee shop (warkop) hangout culture has become a prominent social phenomenon among urban youth. This activity not only functions as a form of recreation and social interaction but also often fosters excessive consumerist behavior. This study aims to analyze the dynamics of Islamic counseling in responding to the warkop hangout culture that influences youth consumerism. The research employed a qualitative phenomenological approach, utilizing observation, in-depth interviews, and documentation with students and young workers in several popular coffee shops. The findings reveal that while warkop hangouts provide social values, identity, and peer relations, they also contribute to increased spending and a show-off lifestyle. Islamic counseling, grounded in the Qur’an, Hadith, and the principle of tazkiyatun nafs, can serve as a mental-spiritual development strategy to reduce consumerist tendencies. In conclusion, the hangout culture can be transformed into a positive space when integrated with Islamic approaches, thus requiring counselors, religious leaders, and educators to utilize this phenomenon as an avenue for informal da’wah and counseling